Análise econômica de milho convencional e transgênico em dois sistemas de preparos de solo - Silva, Paulo R.A. [UNESP]; Correia, Tiago P. Da S. [UNESP]; De Sousa, Saulo F.G. [UNESP]; Millani, Thais M. [UNESP] (FapUNIFESP (SciELO), 2015)
Corn is an agricultural crop of major importance regarding its wide use and production forms. Given these background, this work aimed at analyzing economically the corn production chain with different hybrids and soil tillage systems. The study was carried out at the Experimental Farm of Lageado, located in the College of Agricultural Sciences/UNESP, campus in Botucatu-SP, Brazil. We analyzed two corn hybrids, one conventional and another transgenic, on soil prepared by conventional cultivation practices and minimum cultivation. The same tractors, implements, and fertilizers were employed for both tillage systems. We evaluated operating costs, input costs, gross income, net income, as well as benefit and cost ratio of both cropping systems. Therefore, we concluded that transgenic corn provides reduced operating costs and inputs, enabling higher yield, net income and benefit/cost relationship when cropped with minimum cultivation practices.
Economic analysis of conventional and transgenic corn under two soil tillage systems
Keywords: Biotechnology; Operational cost; Yield